Validitas instrumen strategi card sort pada pembelajaran - Khoiro, Miftakhul (ARKA INSTITUTE, 2022)
Instruments are materials used or needed to collect student data in order to test the level of students' knowledge of the material presented. Subjects that are suitable for the instrument are PPKn. Before the learning is carried out, learning must be in accordance with the Covid-19 situation in Indonesia, namely by using the card sort strategy. To ensure the quality of the strategy, a special study is needed to assess its validity. This study aims to assess aspects of the validity of the card sort instrument. This research is a descriptive quantitative study that presents the data from the validation results and the validator's suggestions on the validity of the card sort instrument. The validator consists of two people, namely one lecturer at PGRI Adi Buana University Surabaya and the other a grade 4 elementary school teacher. The instruments used are student responses and activities. The results of the analysis of the validation sheet show that in general the card sort strategy meets the valid criteria.